Urdu ka guldasta Champa - Fozia Ahsan Farooqui (Karachi: Oxford university press, 2023)
Urdu Ka Guldasta (UKG) is a series of books that has enriched the minds of students and teachers like. This Khususi Isha$1 (Bat (special edition) is aligned with Single National Curriculum 2022 and has been designed to enhance the learning of students and offering a higher level of interest. The main emphasis of this edition are: Alignment with the SNC 2022: The layout and design of the textbooks are prepared in light of the suggestions of Single National Curriculum (SNC) 2022. The pre-primary books are in line with Early Childhood Care and Education (ECCE) 2022 and primary books comply with the SNC (2022) for the Urdu language. Each book is divided into three terms and each term has a significant number of lessons including prose and poem with SLOs and keywords used in the lesson are included. Phonics and sight-reading methods are used where essential. Effective changes have been made in activities and exercises; the addition of objective questions is one of them. Combination of MCQs, objective questions and comprehension questions with each lesson. Brainstorming questions and additional information boxes with lessons to enhance the curiosity and engagement of children towards the lesson. Guidelines for teachers with every lesson are also added to assist teachers in achieving lesson$1 (Bs outcomes. Word bank with respect to lesson sequence and with meanings are included at the end of each book for the ease of students. Focus on all Four Language Skills: Listening and speaking: group activities and application of these skills at different occasions and their development has been ensured. Reading: auditory and visual teaching methods have been employed. Principles of the auditory system of Urdu have been gradually introduced in primary classes. Writing: Urdu is normally written in Nastaleeq font. To elaborate on the minute details of this writing, the simple yet comprehensive method has been used. Urdu Grammar: To familiarize Urdu as the national language, simple and interesting activities have been organised. Care has been taken to ensure the ease of users whose mother tongue is not Urdu. Development of Comprehension Skills: Bloom$1 (Bs Taxonomy has been introduced in the proper sequence of remembering, understanding, applying, analysing, evaluating, and creating. Creative Writing: Starting from making small sentences in pre-primary to making simple couplets and then writing essays and poetry in grade 5$1 (Bhas been made very simple and comprehensive. Includes stimulating students to write an account of an event, story writing, letters and recording memorandums in the diary.s
Keywords: Urdu